2017
DOI: 10.1021/jacs.7b00261
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Sn-Catalysis for Electrochemical Reduction of CO2 to CO via the Core/Shell Cu/SnO2 Structure

Abstract: Tin (Sn) is known to be a good catalyst for electrochemical reduction of CO to formate in 0.5 M KHCO. But when a thin layer of SnO is coated over Cu nanoparticles, the reduction becomes Sn-thickness dependent: the thicker (1.8 nm) shell shows Sn-like activity to generate formate whereas the thinner (0.8 nm) shell is selective to the formation of CO with the conversion Faradaic efficiency (FE) reaching 93% at -0.7 V (vs reversible hydrogen electrode (RHE)). Theoretical calculations suggest that the 0.8 nm SnO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
489
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(507 citation statements)
references
References 27 publications
16
489
1
1
Order By: Relevance
“…[1][2][3] Electrochemical reduction of CO 2 has attracted wide attention because it can convert and store renewable energy resources, such as solar and wind energies, in the form of chemical energy. However, as ingle catalyst showing activity in both solvent types is still rare, to the best of our knowledge.W ed eveloped ac ore-shell-structured AgNW/NC700 composite using aA gn anowire( NW) core encapsulated by aN -doped carbon (NC) shell at 700 8C.…”
mentioning
confidence: 99%
“…[1][2][3] Electrochemical reduction of CO 2 has attracted wide attention because it can convert and store renewable energy resources, such as solar and wind energies, in the form of chemical energy. However, as ingle catalyst showing activity in both solvent types is still rare, to the best of our knowledge.W ed eveloped ac ore-shell-structured AgNW/NC700 composite using aA gn anowire( NW) core encapsulated by aN -doped carbon (NC) shell at 700 8C.…”
mentioning
confidence: 99%
“…Besides pure metals, alloying of two different metals is explored so as to tune the binding strength of key intermediates through geometric and electronic effects, and therefore optimize the CO 2 RR reaction activity and selectivity. Thus far, most research attention has been focused on Cu‐based alloys, such as Cu–Au, Cu–Pd, Cu–In and Cu–Pt and Cu–Sn, and some showed very exciting results 92, 93, 94, 95, 96. It can be reasonably expected that the alloying strategy would soon be expanded to other combination for better possibilities.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…For instance, Yu and his team [5] report that copper nanoparticle interspersed MoS 2 nanoflowers facilitate CO 2 electroreduction to hydrocarbon, such as CH 4 and C 2 H 4 with high FE at low overpotentials. Sun et al [6] demonstrated a new strategy of controlling synergistic effect between Cu and SnO 2 in the core/shell Cu/SnO 2 structure to achieve selective electrochemical reduction of CO 2 to CO with FE reaching 93% at −0.7 V vs. reversible hydrogen electrode (RHE) in 0.5 M KHCO 3 .…”
Section: Introductionmentioning
confidence: 99%